How do new statutory regulations on accessibility increase the chances of social and professional activation of people with disabilities? - Sieradzki, Piotr (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The article asks to what extent the dissemination and introduction of accessibility standards can result in the social and professional activation of people who have so far remained on the sidelines of public life due to various deficits of an institutional, social and personal nature? The theoretical basis for these considerations is the social model of disability, which locates the problem of participation of MSPs in public life in the organization of society and in the properties of the environment in which such people function. The empirical basis for this article will be the authors participation as a researcher and auditor in research and implementation projects on accessibility in 2018–2022.This article is undoubtedly one of the first to seek the relationship between accessibility standards and the level of social and professional activation of people with disabilities and special needs. The topic is dynamic for several reasons. First, the process of adaptation itself in the year of writing the article (2023) is in its early stages. Secondly, the standards themselves will be developed for the various departments of the public sector and thus optimal solutions will arrive. Thirdly, research on accessibility and activation will become more advanced and capable of monitoring this complex – non-linear development. At this point it can be concluded, that the relationship between these two spheres: accessibility – activation is positive, but still indirect and without solving the many problems.